TRANSGENDERS COMPLIANCE FACTORS IN CARRYING OUT VOLUNTARY COUNSELING AND TESTING (VCT) SERVICES DURING COVID-19 PANDEMIC - Pangestu Prabawati; Riska Ratnawati; Suhadi Prayitno; Karina Nur Ramadhanintyas (Media Bina Ilmiah, 2022)
VCT test services play a role in improving the health status of the community, both physically and mentally through pre-counseling VCT tests to clients or patients as well as being the main network for the spread of HIV/AIDS in Indonesia. In the era of the Covid-19 pandemic, there is no reason to carry out VCT tests on transgender because the government continues to urge to implement health protocols to break the chain of transmission of Covid-19. This study aims to determine the factors that influence compliance with VCT test services for transgender during the Covid-19 pandemic in Madiun Regency and support the recovery of people with HIV/AIDS.This research is a quantitative research with a cross sectional approach, which produces data from interviewing respondents through a questionnaire research instrument. Sampling was conducted by random sampling using the Slovin formula with a sample size of 69 respondents. Thematic analysis was performed using the Chi-Square test.Based on the theory of Lawrence Green Behavior Causes, there are factors that can influence behavior. Predisposing Factors, Knowledge, Attitudes; Enabling factors, VCT test services; Reinforcing factors, family support, peer support, health worker support.In this study, all factors affect the compliance of VCT test services during the Covid-19 pandemic. In addition, the researchers found that, family support factors, the role of the community and local government. The results of this study are expected to be used as supporting data and references in improving the quality of VCT test services for at-risk groups